Identification of groundwater level decline in Zagreb and Samobor-Zaprešić aquifers since the sixties of the twentieth century (Rudarsko-geološko-naftni zbornik, 2018)
This study examines historically measured groundwater levels on observation wells of Zagreb and Samobor-Zaprešić aquifers since the 70-ies of the 20th century until today. The analysis also entails older groundwater level maps dating from the 60-ies of the previous century, which offer additional insights into the historical groundwater levels. The analysis of the existing groundwater levels and historical groundwater levels has identified changes of those levels in certain areas of the aquifer, special reference being taken to developments which, with time, led to deceleration of negative trends of groundwater levels in certain parts of the aquifer. The most significant such developments in the past 50 years or so are the construction of the weir of the Zagreb cogeneration plant (TE-TO) in the Sava river and occurrence of hydrologically above-average favourable years like 2013/2014, which have been separately analysed. The analysis has found that today's groundwater levels in Zagreb and Samobor-Zaprešić aquifers are generally lower by approximately 3 to 6 m in comparison with the historical levels from the 60-ies of the last century.